Essential oils, phytochemicals and bioactivity studies of Curcuma aeruginosa Aff. and Kaempferia rotunda Linn - Che Jamalluddin, Nur Adilla (2014)
The essential oils, phytochemicals and bioactivities of Curcuma aeruginosa Aff., known as temu hitam and Kaempferia rotunda Linn. or kunyit putih have been studied. Hydrodistillation of the fresh rhizomes of C. aeruginosa and K. rotunda gave 77.1% and 89.3% oils respectively. These oils were analyzed by GC and GCMS. The chemical compositions were identified by comparison of the mass spectral data of Wiley Library and Kovats Indices with literature values. A total of 42 components were identified from C. aeruginosa with epicurzerenone (19.47%) as the major constituent followed by 1,8-cineole (15.89%), trans-ß-farnesene (9.75%), ß- elemene (6.61%) and camphor (5.84%). K. rotunda essential oil was found to have 33 components with high concentration of benzyl benzoate (31.48%), bornyl acetate (5.56%), camphor (5.45%) and camphene (5.04%). Extractions by soxhlet apparatus were carried out on the dried samples to get the crude extracts. Fractionation and purification on the crude extracts of both species resulted in the isolation of sesquiterpenoids, cyclohexane oxide, esters and fatty acid. The structures of the isolated compounds were identified by spectroscopic techniques including IR and NMR (1D and 2D) spectroscopies and mass spectrometry. Seven sesquiterpenoids were isolated from C. aeruginosa and identified as curzerenone, furanodienone, germacrone, dehydrocurdione, curcumenone, curcumenol and curzeone. Four compounds were successfully isolated from K. rotunda and characterized as benzyl benzoate, crotepoxide, lignoceric acid and stigmasterol. The crude extracts, essential oils and several pure phytochemicals were screened for antibacterial and antityrosinase activities. Disc diffusion method followed by minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) against Gram positive and Gram negative bacteria were used for antibacterial assay. All the essential oil, crude extracts and compounds of C. aeruginosa and K. rotunda exhibited weak to inactive activity against the entire tested microorganisms. Modified dopachrome method with L-DOPA as the substrate was chosen to screen the antityrosinase activity. Among all the tested samples, the essential oil of C. aeruginosa possessed the highest activity with 15.62% inhibition against the mushroom tyrosinase. This inhibition value was far lower compared to the standard kojic acid which showed 81.81% inhibition.